The Direct and Indirect Relationship Between Social Cognition and Psychosocial Dysfunction in Major Depressive Disorder - Knight, Matthew J.; Baune, Bernhard T. (Frontiers in Psychiatry, 2019)
Background: Recent evidence suggests that depressed patients experience social cognitive deficits (e.g., poor affect recognition). However, very little is known regarding the contribution of social cognitive deficits to psychosocial dysfunction (e.g., occupational functioning). In particular, the mechanistic roles of depression severity and cognitive deficits (e.g., memory) in this domain have not been explored. The current study evaluated the extent to which mood symptoms and cognitive deficits provide a mechanistic explanation for the relationship between social cognitive and psychosocial deficits in Major Depressive Disorder (MDD). Methods: Data were obtained from 111 participants with MDD (75 Female, mean age= 35, 84% Caucasian, 12% Asian, 4% Other) in the Cognitive Function and mood study (CoFaMS), a cross sectional study of mood, social cognition, cognition, and psychosocial functioning in mood disorders. Social cognitive abilities were assessed using the Social Perception subtest of the Wechsler Adult Intelligence Scale, and psychosocial dysfunction was clinically evaluated with the Functioning Assessment Short Test (FAST). Results: Cognitive deficits and mood symptoms did not significantly mediate relationships between social cognitive ability and psychosocial dysfunction. The exception was executive function, which mediated an indirect relationship between meaning interpretation (i.e., theory of mind) and self-perceived cognitive dysfunction. Conclusion: The results suggest that the relationship between social cognitive deficits and psychosocial dysfunction is not mechanistically explained by mood symptoms or non-social cognition. Development of treatment strategies targeting social cognitive deficits in patients with MDD is warranted.